2012
DOI: 10.1111/j.1365-2222.2012.04031.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplementation in early infancy modulates developing infant immune responses

Abstract: Postnatal fish oil supplementation increased infant n-3 polyunsaturated fatty acid (PUFA) levels and associated with lowered allergen-specific Th2 responses and elevated polyclonal Th1 responses. Our results add to existing evidence of n-3 PUFA having immunomodulatory properties that are potentially allergy-protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 49 publications
6
75
2
5
Order By: Relevance
“…Three of these studies found beneficial effects of supplementation on immune markers [101,102] or allergic diseases [103]. D'Vaz et al [102] randomized 420 term infants with a high risk of allergy to a daily supplement of fish oil (280 mg DHA, 100 mg EPA) or placebo from birth until 6 months of age. They found lower allergen-specific Th2 responses and elevated Th1 responses in the fish oil group, suggesting a potentially allergy-protective effect on immune function [102].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these studies found beneficial effects of supplementation on immune markers [101,102] or allergic diseases [103]. D'Vaz et al [102] randomized 420 term infants with a high risk of allergy to a daily supplement of fish oil (280 mg DHA, 100 mg EPA) or placebo from birth until 6 months of age. They found lower allergen-specific Th2 responses and elevated Th1 responses in the fish oil group, suggesting a potentially allergy-protective effect on immune function [102].…”
Section: Resultsmentioning
confidence: 99%
“…D'Vaz et al [102] randomized 420 term infants with a high risk of allergy to a daily supplement of fish oil (280 mg DHA, 100 mg EPA) or placebo from birth until 6 months of age. They found lower allergen-specific Th2 responses and elevated Th1 responses in the fish oil group, suggesting a potentially allergy-protective effect on immune function [102]. Improved immune parameter responses after LC-PUFA supplementation were also observed in formula-fed term infants at 16 weeks of age [101].…”
Section: Resultsmentioning
confidence: 99%
“…The other major study (n=420) commenced fish oil supplementation much earlier, in the first week of life [65]. While the intervention increased n-3 PUFA levels and was associated with lower allergen-specific Th2 responses and elevated polyclonal Th1 responses by 6 months of age [66], there was no effect on the risk of eczema or other outcomes in the primary intention-to-treat analysis [65]. A lower risk of eczema and recurrent wheeze in the children who had higher n-3 PUFA levels suggest that there was still some immunomodulatory influence of these fatty acids.…”
Section: N-3 Pufasmentioning
confidence: 98%
“…They reported several improvements in markers of immune function with fish oil supplementation during the first 6 months of life (Table 2) (D'Vaz et al 2012a). Among them, there was a suggested lower allergic response (lower production of IL-13) to house dust mite and a higher Th1 response (IFN-␥ and TNF-␣) after T-cell stimulation in the fish oil group compared with the placebo (D'Vaz et al 2012a), indicative of enhanced immune maturation.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of the interventions varied from 4 weeks (1 month) to 12 months and 2 studies included infants at high risk of atopic diseases. Two published studies came from the same group in Australia (D'Vaz et al 2012a(D'Vaz et al , 2012b, 1 in France (Lapillonne et al 2014), 1 in Spain (Pastor et al 2006), 1 in the United States (Dallas) (Birch et al 2010), and 4 studies from the same group in Canada (Field et al 2000(Field et al , 2008a(Field et al , 2008b(Field et al , 2010. Of the 9 trials, markers of immune function or incidence of allergic and atopic diseases was the primary outcome of 5 trials, the secondary outcome of 2 trials, and this information was unspecified for 2 articles.…”
Section: Introductionmentioning
confidence: 99%